Pleistocene Pb isotope records of crust Haxby from PS75/247-2 - Huang Huang; Martin Frank (PANGAEA, 2025)
Lead (Pb) isotope measurements are performed in the ferromanganese crust PS75/247-2, dredged on the southern flank of Haxby Seamount in the Pacific sector of the SO. We apply laser ablation coupled with multiple-collector inductively coupled plasma mass spectrometry (LA-MC-ICPMS) and two-dimensional (2D) mapping techniques. This combined novel approach enables us to confidently resolve orbital Pb isotope variations for the past 800 ka. Pb isotope is a sensitive water mass tracer and our results reveal systematically higher 208Pb/206Pb ratios during lukewarm interglacials than during more recent interglacials while 206Pb/204Pb ratios remained similar, suggesting reduced vertical deep-water mixing in the Southern Ocean during lukewarm interglacials. By enhancing deep-sea carbon sequestration and thereby lowering atmospheric CO2, strengthened deep Southern Ocean stratification likely imposed critical impacts on the lukewarm interglacial climates.